A Reflective Terahertz Point Source Meta-Sensor with Asymmetric Meta-Atoms for High-Sensitivity Bio-Sensing - Luwei Zheng; Kazuki Hara; Hironaru Murakami; Masayoshi Tonouchi; Kazunori Serita (Biosensors)
Biosensors operating in the terahertz (THz) region are gaining substantial interest in biomedical analysis due to their significant potential for high-sensitivity trace-amount solution detection. However, progress in compact, high-sensitivity chips and methods for simple, rapid and trace-level measurements is limited by the spatial resolution of THz waves and their strong absorption in polar solvents. In this work, a compact nonlinear optical crystal (NLOC)-based reflective THz biosensor with a few arrays of asymmetrical meta-atoms was developed. A near-field point THz source was locally generated at a femtosecond-laser-irradiation spot via optical rectification, exciting only the single central meta-atom, thereby inducing Fano resonance. The reflective resonance response demonstrated dependence on several aspects, including structure asymmetricity, geometrical size, excitation point position, thickness and array-period arrangement. DNA samples were examined using 1 μL applied to an effective sensing area of 0.234 mm2 (484 μm × 484 μm) for performance evaluation. The developed Fano resonance sensor exhibited nearly double sensitivity compared to that of symmetrical sensors and one-gap split ring resonators. Thus, this study advances liquid-based sensing by enabling easy, rapid and trace-level measurements while also driving the development of compact and highly sensitive THz sensors for biological samples.